Difference in interoception between long-distance runners and sprinters: An event-related potential study - Hirao, T.; Vogt, T.; Masaki, H. (Medicine & Science in Sports & Exercise, 2020)
Purpose: Interoception is a sense of the physiological state of one`s body. Interoception that is generated by processing physiological information in the insular cortex plays an important role in achieving optimal performance in competitive sports. This study aimed to reveal the difference in interoceptive ability between long-distance runners and sprinters and its neural correlates by recording the stimulus-preceding negativity (SPN) that is generated from the insular cortex. Based on previous findings, we predicted that long-distance runners would show better interoceptive ability and larger SPNs compared with sprinters. Method: We used a questionnaire and a heartbeat counting task to evaluate the interoceptive sensitivity and accuracy, respectively, of both long-distance runners and sprinters. We recorded SPNs during the execution of a time estimation task where participants estimate 3 s by pressing a button. Results: Results of the questionnaire revealed that sprinters exhibited a higher interoceptive ability associated with attention control of their own bodies than did long-distance runners. Sprinters also showed a larger SPN over the left centroparietal regions compared with long-distance runners. Conclusion: In contrast to our prediction, sprinters exhibited a superior interoceptive ability and a greater activity of the insular cortex relative to long-distance runners. These results suggest that sprinters might be more susceptible to their internal bodily signals compared with long-distance runners, exhibiting greater activation of the anterior insula.